Penanggualangan Bencana Melalui Program Sekolah Pendidikan Aman Bencana (SPAB) di Kota Malang - Deri Fikri Haikal; Yana S. Hijri; Muhammad Kamil (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2021)
Malang city includes the city of education and through the application of Inarisk Personal as one of the areas prone to disasters, especially floods of high class categories and earthquakes of moderate grade categories. Therefore, an effort is needed to educate school residents both students and educators in terms of disaster mitigation through the Disaster Safe Education School (SPAB) program, considering that students have the right to sustainability by providing an atmosphere and environment that ensures the learning process, health, safety, and safety of students are guaranteed at all times and also children have specific needs in the face of disaster hazards and all such efforts are carried out by inviting children to participate actively. The method used in this research is qualitative method with descriptive approach according to Creswell that begins with assumption, interpretation/ theoretical, and research problem that examines how individual or group interpret social or humanitarian problems. The results showed that in the implementation of the Sekolah Pendidikan Aman Bencana (SPAB), school residents, both educators and especially learners, know what to handle at the time of a disaster through a dissemination stage consisting of socialization, visualization and also disaster simulation, and there is a stage of monitoring or monitoring to see the extent to which the output is conveyed well to learners , and program evaluation is related to measuring the extent of students' understanding after the implementation of the SPAB program.